Reconciling fiscal consolidation with growth and equity - Cournède, Boris (OECD Publishing, 2014)
Despite sustained efforts made in recent years to rein in budget deficits, a majority of OECD countries still face substantial public finance consolidation needs. While essential to avoid the disruption and large costs ultimately associated with unsustainable public finances, fiscal consolidation complicates the task of achieving other policy goals. In most cases, it weighs on demand in the short term. And, if too little attention is paid to the mix of instruments used to achieve consolidation, it can undermine long-term growth, exacerbate income inequality and slow the process of global rebalancing. It is therefore important for governments to adopt consolidation strategies that minimise these adverse side-effects. The analysis proposes consolidation strategies that take into account other policy goals as well as country-specific circumstances and preferences. To do so, increases in particular taxes and cuts in specific spending areas are assessed for their effects on short- and long-term growth, income distribution and external accounts. The results of detailed illustrative simulations indicate that a significant number of OECD countries may have to raise harmful taxes or cut valuable spending areas to deliver sufficient consolidation, underscoring the need for structural reforms to counteract these side-effects. The results are robust to an extensive range of sensitivity checks